Detection of VLF and LF emissions of fluorescent light for efficient management of power consumption - Othman S.S.B.S.; Hock G.C.; Nordin F.H.B.; Mustafa N.B.B.A.; Balasubramaniam N.; Sharrif Z.A.M. (Institute of Physics Publishing, 2023)
In this research work, a detection probe of Very Low Frequency and Low Frequency (LF) emissions of fluorescent light is developed by using low cost loop antenna. The developed loop antenna is able to operate at VLF and LF bandwidth. The developed antenna is tested and measured with signal generator and oscilloscope in order to verify the usefulness of antenna. The developed antenna is subsequently used to detect the signal emitted by the fluorescent light. The antenna probe is located at different distance in order to obtain the peak voltage of received signal. Besides that, the fluorescent light is switch on and off respectively in order to verify the source of signal. From the oscilloscope, the received signal is operating at approximately 28 KHz. Hence, the developed antenna probe can be used for efficient management of power consumption as 28 KHz signal is detected if the light is on. Published under licence by IOP Publishing Ltd.